Effects of Cry toxins on non-target soil bacteria during a 2-year follow up study - Amina Yaqoob; Ahmad A. Shahid; Ibrahim B. Salisu; Saira Azam; Mukhtar Ahmed; Abdul Q. Rao (Spanish Journal of Agricultural Research, 2019)
Genetically modified (GM) plants with insecticidal Bacillus thuringiensis (Bt) genes are widely accepted but their commercial utilization highlights the biosafety issues worldwide. The risk assessment of GM crops demonstrates their impact on the ecosystem as well as non-target organisms (NTOs). Among the NTOs, plant growth promoting rhizobacteria (PGPR) demand more critical experimental studies as they play a significant role in plant growth. A comparative study of Bt with non-Bt cotton rhizosphere was conducted, on selected bacterial strains. During the course of the study, biochemical characterization, auxin biosynthesis and molecular characterization was done to assess the effect of Bt toxins (Cry1Ac and Cry2A) on non-target PGPR strains. A significant decrease (p<0.05) in phosphatase activity was recorded in some of the experimental bacterial strains as compared to those of control strains. However, no significant differences (p>0.05) were observed in other parameters like bacterial population, colony morphologies as well as biochemical activities. Thus, our study demonstrates the safe plantation of Bt crops with respect to soil bacteria.